Ignacio Prat y la transducción dantesca. - Ghignoli, Alessandro (Astra museum, 2023)
In Spain during the second half of the twentieth century a certain type of poetry was born that did not find the place and the space for the debate that it undoubtedly deserved given its high linguistic and literary value. In this sense, the poetry of the Spanish poet Ignacio Prat deals with those types of writings that flank with experimentalism and with the true avant-garde itself. In this piece of work and through the study of a text entitled “Lineamenta” we will endeavor to show how the presence of a universal poet such as Dante can be perceived in the making and editing of the very text of such a poet. The proximity between literary creation and translation is proven here with the analysis of the poem, which, as we shall see, is influenced by the presence of Dante by a game of intertextual cross-references that achieve to offer us a poem of high communicative content adorned with diachronic literary materials that the Spanish poet can reuse for a text of contemporary poetry.
Política de acceso abierto tomada de: https://revistatransilvania.ro/politica-open-access/
Keywords: Prat, Ignacio (1945-1982) - Crítica e interpretación; Ignacio Prat; Spanish poetry; Transduction; Dante